2002
DOI: 10.1194/jlr.m20063-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

ω-Carboxyl variants of 7-ketocholesteryl esters are ligands for β2-glycoprotein I and mediate antibody-dependent uptake of oxidized LDL by macrophages

Abstract: ␤ 2 -Glycoprotein I ( ␤ 2 -GPI) is a major antigen for anticardiolipin antibodies (aCL, Abs) present in patients with antiphospholipid syndrome. We recently reported that ␤ 2 -GPI specifically binds to oxidized LDL (oxLDL) and that the ␤ 2 -GPI's major ligand, oxLig-1 is 7-ketocholesteryl-9-carboxynonanoate (Kobayashi, K., E. Matsuura, Q. P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
68
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 70 publications
(72 citation statements)
references
References 62 publications
3
68
1
Order By: Relevance
“…Antiphospholipid Abs are directed against epitopes that include proteins such as b2-glycoprotein I (b2GPI) (4)(5)(6), lipids, and protein-lipid complexes. We have demonstrated that anti-b2GPI autoAbs also recognize oxLDL/b2GPI complexes (4,(7)(8)(9)(10). Further, the in vitro macrophage uptake of oxLDL/b2GPI complexes was significantly increased by IgG anti-b2GPI Abs.…”
mentioning
confidence: 75%
See 1 more Smart Citation
“…Antiphospholipid Abs are directed against epitopes that include proteins such as b2-glycoprotein I (b2GPI) (4)(5)(6), lipids, and protein-lipid complexes. We have demonstrated that anti-b2GPI autoAbs also recognize oxLDL/b2GPI complexes (4,(7)(8)(9)(10). Further, the in vitro macrophage uptake of oxLDL/b2GPI complexes was significantly increased by IgG anti-b2GPI Abs.…”
mentioning
confidence: 75%
“…Further, the in vitro macrophage uptake of oxLDL/b2GPI complexes was significantly increased by IgG anti-b2GPI Abs. (4,(7)(8)(9)(10) Thus, findings suggesting that IgG antib2GPI auto-Abs may be proatherogenic renewed interest in the immunologic mechanisms participating in atherogenesis (4,11,12).…”
mentioning
confidence: 99%
“…Native LDL is taken up by specific LDL receptor whereas oxLDL is taken up by scavenger receptors [46]. The presence of β2GPI and IgG β2GPI auto-antibodies increases the macrophage uptake of I131-Cu2+-oxLDL in keeping with a proatherogenic role of IgG anti-β2GPI antibodies [47]. The uptake of the immune complexes is likely mediated by macrophage Fcγ receptors rather than scavenger receptors.…”
Section: Monocytes/macrophages and Atherosclerosismentioning
confidence: 90%
“…OxLig-1 (7-ketocholesteryl-9-carboxynonanoate) is a Cu 2þ -derived LDL ligand for b 2 GPI prepared as previously described (Liu et al 2002). Fifty microliter of 100 mg/ml of oxLig-1 in ethanol were adsorbed by evaporation on a plain polystyrene plate (Immulon 2HB) followed by blocking with 1% BSA for 1 h at room temperature and then washed.…”
Section: Measurement Of Igg Anti-b 2 Gpi -Oxlig-1 Antibodiesmentioning
confidence: 99%
“…Of further interest is the knowledge that b 2 GPI binds to Cu 2þ -oxidised LDL (oxLDL) and that macrophages uptake this complex much faster in the presence of an antibody towards oxLDLb 2 GPI (Hasunuma et al 1997). More recently, this concept has been extended to the complex of b 2 GPI with 7-ketocholesteryl-9-carboxynonanoate (oxLig-1), the very oxLDL-derived moiety that binds b 2 GPI (Liu et al 2002). As antibodies towards b 2 GPI-oxLig-1 are associated with arterial thrombosis in APS (Lopez et al 2003) we herein explored whether antibodies towards anti b 2 GPI-oxLig-1 bore any atherogenic potential in primary APS.…”
Section: Introductionmentioning
confidence: 99%